Photosynthesis Plastid Biology, Energy Conversion and Carbon Assimilation - Eaton-Rye, Julian J.; Tripathy, Baishnab C.; Sharkey, Thomas D.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
Solar energy is the source of almost all life on this Earth. An important factor in increasing the production of biomass, bioenergy and biofuel, which is needed to solve the global energy crisis, is the overall efficiency of photosynthesis. To manipulate overall efficiency we must understand the basic reactions of photosynthesis. This volume (Photosynthesis: Plastid Biology, Energy Conversion and Carbon Assimilation) in the Advances in Photosynthesis and Respiration series provides a comprehensive view of the current understanding of photosynthesis; it is divided into several sections to help the readers see the broad categories of photosynthetic processes. The first twenty-nine chapters in this volume cover the topics central to our current understanding of Photosynthesis. An additional chapter focuses on historical aspects tracing the development of concepts in photosynthesis. A strong evolutionary thread runs through the chapters; evolutionary insights aid in understanding why photosynthesis today has so many of its special properties. In this volume readers will find discussions of the origins of photosynthesis through to the future of photosynthesis, both near term as affected by global change and even further, the prospects for engineering artificial photosynthesis. Readers will learn about bacteria that use just parts of the photosynthetic system found in plants and how duplication and specialization in a small number of progenitor pigments, and proteins, gave rise to the vast array of pigments and proteins that are found in photosynthetic systems today. This book is dedicated to Govindjee, the founding series editor, whose research contributions are enormous, and are included in the last three chapters of this book. This volume will be of interest to advanced undergraduates in plant biology, and plant biochemistry and to graduate students and instructors wanting a single reference volume on the latest understanding of the critical components of photosynthesis. For biologists, biochemists, and biophysicists, this volume will provide quick background understanding for the breadth of issues in photosynthesis that are important in research and instructional settings.
Dedication -- From the Series Editors -- Preface -- The Editors -- Author Index -- Part I: Introduction -- 1. The Photosynthetic World -- Part II: Plastid Biochemistry and Physiology -- 2. Origin, Evolution and Division of Plastids -- 3. Chlorophyll Biosynthesis in Higher Plants -- 4. Biosynthesis, Localization and Concentration of Carotenoids in Plants and Algae -- 5. Assembly of Light Harvesting Pigment-Protein Complexes in Photosynthetic Eukaryotes -- 6. Chlorophyll-Binding Proteins of Higher Plants and Cyanobacteria -- 7. Plant Proteomics and Photosynthesis -- 8. Intracellular Signaling from Plastids to the Nucleus -- 9. The Role of the Envelope Membrane in Chloroplast Glycerolipid Biosynthesis -- 10. Leaf Senescence and Transformation of Chloroplasts to Gerontoplasts -- Part III: Photosynthetic Responses of Plants to Environmental Stress -- 11. The Role of Membrane Structure in Acclimation to Low-Temperature Stress -- 12. Heat Stress: Susceptibility, Recovery and Regulation -- 13. Photosynthetic Responses of Plants to Excess Light: Mechanisms and Conditions for Photoinhibition, Excess Energy Dissipation and Repair -- 14. Light Stress Proteins in Viruses, Cyanobacteria and Photosynthetic Eukaryota -- 15. Environmentally-Induced Oxidative Stress and its Signaling -- Part IV: Energy Conversion -- 16. The Characteristics of Specific Chlorophylls and their Roles in Biogenesis of the Photosynthetic Apparatus -- 17. Photosynthetic Water-Splitting: Apparatus and Mechanism -- 18. Fluorescence Emission from the Photosynthetic Apparatus -- 19. Thermoluminescence -- 20. Regulation of Photosystem II Electron Transport by Bicarbonate -- 21. Cytochrome b6f Complex at the Heart of Energy Transduction and Redox Signaling -- 22. Energy Transduction by the Two Molecular Motors on the F1Fo ATP Synthase -- 23. Electron Transport in Leaves: A Physiological Perspective -- 24. Towards Artificial Photosynthesis. Part V: Carbon Assimilation, Sucrose Synthesis and Transport -- 25. The Uptake of CO2 by Cyanobacteria and Microalgae -- 26. Autotrophic Carbon Dioxide Fixation -- 27. Photosynthetic Sucrose Biosynthesis: An Evolutionary Perspective -- 28. Sucrose Transport in Higher Plants: From Source to Sink -- Part VI: Climate Change and Photosynthesis -- 29. Photosynthesis in CO2 Rich Atmosphere. Part VII: Historical Perspective -- 30. Early Pioneers of Photosynthesis Research -- Part VIII: The Career of Govindjee -- 31. Contributions of Govindjee 1956-1969 -- 32. Contributions of Govindjee 1970-1999 -- 33. Contributions of Govindjee 2000-2010 -- Index.
Keywords: Life sciences; Biochemistry; Botany; Plant physiology; Life Sciences; Plant Sciences; Plant Physiology; Plant Biochemistry